Kalām-i Qatīl Šafāʾī - Šafāʾī, Qatīl,Argalī, Fārūq (Farīd Bukd́ipo, 2005)
Gajar – Guftgū – Rauzan – Jhūmar – Mut̤ribah Selected poems of an Urdu poet
Poems. - Previously published as independent works. - In arab. Schrift, Urdu
Keywords: Urdu poetry